The Problematika kebijakan ekonomi di tengah Resesi Ekonomi dan dampaknya terhadap dunia pendidikan.: Problematika kebijakan ekonomi di tengah Resesi Ekonomi dan dampaknya terhadap dunia pendidikan. - Linda Juliharti; Rusdinal; Hadiyanto (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
After the Covid – 19 Pandemic ended, there were very significant changes in various ways. One of the things that has changed is in the economic field. The pandemic has thrown the economy into disarray because human mobility is limited, so advancing the economy is very difficult. To overcome this, some countries have adopted a policy of raising interest rates simultaneously, which has implications for financial market crises and economic weakness, known as an economic recession. This has an indirect impact on the world of education. Because education cannot be separated from the economy, education can run smoothly if the economy is also running smoothly, but now there is a gap that causes problems in the world of education. The purpose of this article is to look at the problems that occurred in the world of education when these economic policies were implemented so that the term economic recession emerged. The author will try to find solutions to these problems from various scientific references, so hopefully we can overcome these problems as best we can. This research method is a survey and field study with data collection techniques is by observation and qualitative descriptive. The results obtained are that there are many problems in the world of education after the economic policy is implemented. In fact, this impact starts from the educational actors who are above and even reaches the educational actors who are below, namely students.